Targeted downregulation of platelet CLEC-2 occurs through Syk-independent internalization - Lorenz, Viola (Blood, 2015)
Platelet aggregation at sites of vascular injury is not only essential for hemostasis, but may also cause acute ischemic disease states such as myocardial infarction or stroke. The hemi-immunoreceptor tyrosine-based activation motif–containing C-type lectinlike receptor 2 (CLEC-2) mediates powerful platelet activation through a Src- and spleen tyrosine kinase (Syk)–dependent tyrosine phosphorylation cascade. Thereby, CLEC-2 not only contributes to thrombus formation and stabilization but also plays a central role in blood-lymphatic vessel development, tumor metastasis, and prevention of inflammatory bleeding, making it a potential pharmacologic target to modulate these processes. We have previously shown that injection of the anti–CLEC-2 antibody, INU1, results in virtually complete immunodepletion of platelet CLEC-2 in mice, which is, however, preceded by a severe transient thrombocytopenia thereby limiting its potential therapeutic use. The mechanisms underlying this targeted CLEC-2 downregulation have remained elusive. Here, we show that INU1-induced CLEC-2 immunodepletion occurs through Src-family kinase–dependent receptor internalization in vitro and in vivo, presumably followed by intracellular degradation. In mice with platelet-specific Syk deficiency, INU1-induced CLEC-2 internalization/degradation was fully preserved whereas the associated thrombocytopenia was largely prevented. These results show for the first time that CLEC-2 can be downregulated from the platelet surface through internalization in vitro and in vivo and that this can be mechanistically uncoupled from the associated antibody-induced thrombocytopenia.